Readymade–Human: Principles of Artistic and Theoretical Work of Robert Cyprich - Ján KRALOVIČ (Sztuka i Dokumentacja)
The study "Readymade – Human: Principles of Artistic and Theoretical Work of Robert Cyprich" examines the theoretical and artistic work of the prominent Slovak neo-avant-garde artist and theorist Robert Cyprich (1951-1996). In the early stages of his work, he had an intense collaboration with musicologist and conceptual artist Milan Adamčiak. The first part of the text clarifies some of their joint activities as well as their publishing initiatives (the magazine Experiment). In the late sixties, Cyprich met artist Alex Mlynárčik, and together they carried out several happenings (such as Festival of Snow in 1970, Day of Joy – If All the Trains in the World in 1971, Eva's Wedding in 1971 etc.). The core of the study focuses on Cyprich's work, which was based on exploring the concepts of society and socialist art. He understood it as an emancipatory tool for society and connected this understanding with various participatory initiatives. The concept of the 'readymade-human' appears primarily in his letters. It is focused on the activation of the individual and their placement into new contexts and situations. Cyprich's correspondence is a valuable testament to his reflections on art and society, as well as his artistic concepts and plans, many of which remained unrealized. Cyprich made a significant mark on the Czechoslovak art scene through his samizdat texts and by disseminating and translating works within the Pro Arte Nova series.